2013 IEEE International Symposium on Hardware-Oriented Security and Trust (HOST) 2013
DOI: 10.1109/hst.2013.6581574
|View full text |Cite
|
Sign up to set email alerts
|

On hardware Trojan design and implementation at register-transfer level

Abstract: Abstract-There have been a number of hardware Trojan (HT) designs at register-transfer level (RTL) in the literature, which mainly describe their malicious behaviors and trigger mechanisms. Generally speaking, the stealthiness of the HTs is shown with extremely low sensitization probability of the trigger events. In practice, however, based on the fact that HTs are not sensitized with verification test cases (otherwise their malicious behaviors would have manifested themselves), designers could focus on verifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 8 publications
0
50
0
Order By: Relevance
“…As a result, the extensive simulation/emulation is likely to detect this type of HTs. From this perspective, bug-based HT is usually not a good choice for attackers in terms of the stealthy requirement, and almost all HT designs appeared in the literature (e.g., [3,[11][12][13][16][17][18]) belong to the parasite-based type, as discussed in the following.…”
Section: Bug-based Htmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, the extensive simulation/emulation is likely to detect this type of HTs. From this perspective, bug-based HT is usually not a good choice for attackers in terms of the stealthy requirement, and almost all HT designs appeared in the literature (e.g., [3,[11][12][13][16][17][18]) belong to the parasite-based type, as discussed in the following.…”
Section: Bug-based Htmentioning
confidence: 99%
“…However, the fact that the effectiveness of [11] relies on HT implementation style enables the simple attack. That is, it is fairly easy to modify the implementation of the HT so that no signal pairs are equal to each other during verification (an example is given in Section 3.2), which has been shown in [12,13].…”
Section: Verification For Hardware Trustmentioning
confidence: 99%
See 1 more Smart Citation
“…A true random number generator (TRNG), for example, is a non-deterministic IP core since its output cannot be predicted and verified by logic testing against an expected output. 3 Any St Trojan in such a core is considered H N D . A pseudo random number generator (PRNG), on the other hand, is considered a deterministic IP core as its output depends upon the initial seed and is therefore predictable by a logic based testing tool (hence H D ).…”
Section: H D Vs H N D Hardware Trojansmentioning
confidence: 99%
“…Hicks et al [2] proposed Unused Circuit Identification (UCI) which centers on the fact that the HT circuitry mostly remains inactive within a design, and hence such minimally used logic can be distinguished from the other parts of the circuit. However later works [3], [4] showed how to design HTs which can defeat the UCI detection scheme. Zhang et al [5] and Waksman et al [6] proposed detection schemes called VeriTrust and FANCI respectively and showed that they can detect all HTs from the TrustHub [7] benchmark suite.…”
Section: Introductionmentioning
confidence: 99%